Antibiotics supplemented culture media can eliminate non-specific bacteria from human semen during sperm preparation for intra uterine insemination - D. M. A. B. Dissanayake; K A Amaranath; R. R. D. P. Perera; P S Wijesinghe (Wolters Kluwer Medknow Publications, 2014)
Rationale: Bacterial flora can be isolated from many semen samples of subfertile males. Bacteriospermia can compromise the outcome of intra uterine insemination (IUI) by contaminating the post-processed sperm sample. Objectives: The objective of the present study is to determine the efficacy of penicillin and streptomycin in eliminating the bacteria from semen samples in the sperm processing procedure, and to assess the effects of antibiotics on sperm motility, survivability, and pregnancy rates. Design and Settings: A prospectively controlled study was carried out using couples undergoing IUI with their informed consent. Intervention: Sperm processing using the swim-up technique in penicillin and streptomycin supplemented culture medium. Subjects And Methods: Couples were consecutively allocated in two groups for sperm processing (a) Group AB+ (antibiotics supplemented culture medium, n = 33) and (b) Group AB− (antibiotic free culture medium, n = 33). Semen culture was performed before and after sperm processing. Sperm motility was assessed immediately after processing and after 24 h of incubation. Results: Bacterial isolates were found in 20 (60.6%) and 22 (66.1%) of samples before processing in Groups AB+ and AB− respectively. Addition of antibiotics resulted in completely eliminating non-specific bacteria from semen samples without affecting sperm motility. In vitro survival rate of sperm enhanced in AB+ group compared with AB− group (motile sperm after 24 h), 62.21% (standard deviation [SD]: 37.27) versus 41.36% (SD: 30.78), P = 0.012. Pregnancy rate, was comparable between two groups (9% in Group AB+ vs. 6% in Group AB−, P = 0.45). Conclusion: Penicillin streptomycin combination could completely eliminate non-specific bacteria from semen samples during sperm processing in this population. The types of antibiotics and dosage used did not seem to have any harmful effects on human sperm.